2017
DOI: 10.1126/scisignal.aaf7478
|View full text |Cite
|
Sign up to set email alerts
|

AMPK promotes mitochondrial biogenesis and function by phosphorylating the epigenetic factors DNMT1, RBBP7, and HAT1

Abstract: Adenosine monophosphate (AMP)–activated protein kinase (AMPK) acts as a master regulator of cellular energy homeostasis by directly phosphorylating metabolic enzymes and nutrient transporters and by indirectly promoting the transactivation of nuclear genes involved in mitochondrial biogenesis and function. We explored the mechanism of AMPK-mediated induction of gene expression. We identified AMPK consensus phosphorylation sequences in three proteins involved in nucleosome remodeling: DNA methyltransferase 1 (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 41 publications
7
141
1
2
Order By: Relevance
“…Indeed, mice lacking IL-6 present lower activity of AMPK, 28 which regulates cellular energy homeostasis and is involved in mitochondrial biogenesis and function. 29 TNF-α seems to induce the lipolytic process by acting through several intracellular pathways for example, by inhibiting insulin receptor signaling, by counteracting the antilipolytic effect of adenosine on protein G, by reducing Gi-protein content or even by directly inducing the phosphorylation of the protein perilipin and reducing of its expression. 26 As reviewed above, metabolic adaptations promoted by aerobic training involve very complex and integrated mechanisms, which are likely tissue-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mice lacking IL-6 present lower activity of AMPK, 28 which regulates cellular energy homeostasis and is involved in mitochondrial biogenesis and function. 29 TNF-α seems to induce the lipolytic process by acting through several intracellular pathways for example, by inhibiting insulin receptor signaling, by counteracting the antilipolytic effect of adenosine on protein G, by reducing Gi-protein content or even by directly inducing the phosphorylation of the protein perilipin and reducing of its expression. 26 As reviewed above, metabolic adaptations promoted by aerobic training involve very complex and integrated mechanisms, which are likely tissue-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Also, inhibited transmethylation and trans‐sulfuration pathway may also contribute to imbalance the pool of l ‐Met. Our study shows that l ‐Met‐S reversed these by AMPK activation, which inhibits the DNMT1 through phosphorylation of Ser 730 residue of DNMT1 …”
Section: Discussionmentioning
confidence: 99%
“…The effect of AMPK activation on HATs varies, increasing the activity of some HATs and decreasing that of others; thus, metformin may likewise have varying effects. For example, Marin et al reported, using a mouse embryonic fibroblast model, that via AMPK activation, metformin induced HAT1 phosphorylation, increasing its activity. Conversely, in multiple other studies, the phosphorylation of the HATs p300 and the CREB‐binding protein (CBP) by AMPK reduced their activity …”
Section: Metforminmentioning
confidence: 99%
“…Interestingly, these changes were not apparent in patients receiving metformin plus insulin. These changes in methylation may be a result of reduced DNMT activity; activation of AMPK by metformin has been reported to phosphorylate DNMT1 at Ser730 and, consequently, to inhibit its methyltransferase activity . This was associated with a decrease in promoter methylation of 6 target genes in wild type mouse embryonic fibroblasts, but not in AMPK knockout cells or in cells with a DNMT1 Ser730 > Ala730 substitution.…”
Section: Metforminmentioning
confidence: 99%
See 1 more Smart Citation